Immersive Versus Non-immersive Experience: Exploring the Feasibility of Memory Assessment Through 360° Technology - Ventura, Sara; Brivio, Eleonora; Riva, Giuseppe; Baños, Rosa M. (Frontiers in Psychology, 2019)
Episodic memory is essential to effectively perform a number of daily activities, as it enables individuals to consciously recall experiences within their spatial and temporal environments. Virtual Reality (VR) serves as an efficacious instrument to assess cognitive functions like attention and memory. Previous studies have adopted computer-simulated VR to assess memory, which realized greater benefits compared to traditional procedures (paper and pencil). One of the most recent trends of immersive VR experiences is the 360° technology. In order to evaluate its capabilities, this study aims to compare memory performance through two tasks: immersive task and non-immersive task. These tasks differ based on the participant’s view of the 360° picture: (1) head-mounted display (HMD) for immersive task and (2) tablet for non-immersive task. This study seeks to compare how memory is facilitated in both the 360° immersive picture as well as the non-immersive 360° picture. A repeated measure design was carried out in a sample of 42 participants, randomized into two groups of 21. Group 1 first observed Picture A (immersive) followed by Picture B (non-immersive) while Group 2 began with Picture B and then looked at Picture A. Each 360° picture contains specific items with some items appearing in both. Memory evaluation is assessed immediately after the exposure (recall task), then again after a 10-min delay (recognition task). Results reveal that Group 1, which began with the immersive task, demonstrated stronger memory performance in the long term as compared to Group 2, which began with the non-immersive task. Preliminary data ultimately supports the efficacy of the 360° technology in evaluating cognitive function.